Specification Bias and Short-Run Returns to Labour: Some Evidence for the United Kingdom - Ireland, N. J.; Briscoe, G.; Smyth, D. J. (The Review of Economics and Statistics, 1973)
N. J. Ireland, G. Briscoe, D. J. Smyth, Specification Bias and Short-Run Returns to Labour: Some Evidence for the United Kingdom, The Review of Economics and Statistics, Vol. 55, No. 1 (Feb., 1973), pp. 23-27